Somebody Expects You Home Tonight: Exploring Safety Practices in Technical School Shops - Mohammed Auta; Arief Kurniawan (Journal of Vocational Education Studies, 2022)
The study explored safety practices in technical school shops. The area of the study was North-Eastern Nigeria. The study adopted descriptive survey research design and the population of the study comprises of 134 carpentry and joinery Teachers/Instructors, 97 workshop attendants and 783 Carpentry and Joinery Students from the 29 Technical Colleges thereby making a population size of 1014. The instrument used for data collection was a structured questionnaire on a five-point scale adapted from a previous study. The reliability coefficient of the instrument was 0.78. Mean was used to analyze the research questions. Findings from the study indicated that safety practices around Technical School shop environment, and the observation of safety practices by workshop personnel were to a moderately extents. It was recommended among others that School administrators should organize periodic reorientation programmes for carpentry and joinery workshop personnel to reeducate them on the need to strictly comply with all the safety standards guiding carpentry and joinery workshop operations.